2014
DOI: 10.1364/jocn.7.00a190
|View full text |Cite
|
Sign up to set email alerts
|

Predeployment of Regenerators for Fast Service Provisioning in DWDM Transport Networks [Invited]

Abstract: Dense wavelength division multiplexing (DWDM) transport networks are evolving to support dynamic setup/teardown of wavelength services. This is becoming possible mainly via node architectures with flexible add/drop port utilization, where an already deployed transponder can be tuned to any wavelength and configured to transmit/receive via any output/input direction, and advanced control and management software, which provide the means to remotely reconfigure equipment end to end. In long-haul networks, exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
(21 reference statements)
0
18
0
Order By: Relevance
“…Given the limited size of this band, maximizing SE is key to avoiding, or at least postponing, capital-intensive investments in new fiber rollouts, additional optical inline amplifiers, and upgrade of ROADMs. However, network operators have to balance this objective with the need to minimize shorter-term capital expenditures, namely the ones with transponder/regenerator equipment required to support all traffic demands [10,11]. As a result, a transparent network design, where 3R regenerators are avoided, is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…Given the limited size of this band, maximizing SE is key to avoiding, or at least postponing, capital-intensive investments in new fiber rollouts, additional optical inline amplifiers, and upgrade of ROADMs. However, network operators have to balance this objective with the need to minimize shorter-term capital expenditures, namely the ones with transponder/regenerator equipment required to support all traffic demands [10,11]. As a result, a transparent network design, where 3R regenerators are avoided, is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…The reported results showed that the MSU-RP algorithm outperformed all previous approaches. In Reference [18], four strategies for regenerator predeployment in WDM network were presented, starting with a basic uniform distribution of regenerators followed by three topology-based methods that can be enriched with information on network traffic.…”
Section: Related Workmentioning
confidence: 99%
“…Uniform location (UNI) assumes that each node is assigned with the same number of transponders [18]:…”
Section: Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the conventional ROADM, which adopts demux-switch-mux architectures to split and switch wavelengths in color and space respectively [2]- [5], the emergence of Wavelength Selective Switch (WSS) enables the ROADM to exchange wavelength channels in both domains simultaneously [6]- [10]. Since WSS can select arbitrary number of wavelengths from the input port to output fiber independent of wavelengths, the WSS based ROADMs avoids the unnecessary demux-mux process to split each wavelength channels into single instances.…”
Section: Introductionmentioning
confidence: 99%